PCB bioaccumulationin three mullet species — A comparison study - Batista, Joana (2013)
Polychlorinatedbiphenyls(PCBs)arelipophiliccontaminantsthattendtoaccumulateinorganisms.PCBs weredetectedin Chelon labrosus, Liza aurata and Liza ramada, alongdifferentagegroups. L. ramada presentedthehighestconcentration,anditincreasedwithage,whereas C. labrosus and L. aurata concentration remainedconstant. L. ramada high concentrationcanbeattributedtoitsecologicalniche, since thisspeciesisabletoaccumulatePCBsalongitsdifferentagegroupseveninlowenvironmental contamination conditions.PCBs101,118,138,149,153,170and180werethecongenersthatmore contributed tothesespeciescontamination,beingPCB138and153thecongenerswithhigher concentration. Mulletsareedibleinmanycountries,beingimportantin fisheries andaquaculture. L. ramada is themostcommonmulletforcaptureandhumanconsumption.Allspeciespresented concentrations belowtheregulationlimitestablishbytheEuropeanUnion,andthereforesafeforhuman consumption.